Life Orientation as a posthumanist interspace: Reclaiming human-centric higher education in a post-neoliberal South African landscape - de Jager, Sarina; Jarvis, Janet (Critical Studies in Teaching and Learning, 2025)
This article advances a humanistic vision for higher education by reimagining Life Orientation (LO) – a South African school subject often dismissed as marginal – as a vital knowledge interspace within universities. Situated within the context of teacher education, the article critiques the dehumanising effects of neoliberalism and colonial epistemologies, and advocates for a curriculum that foregrounds relationality, ethics, and holistic learning. Drawing on posthumanist, decolonial, and nomadic theory, particularly Braidotti’s work, the paper conceptualises LO as a transdisciplinary site that supports boundary-crossing and inclusive pedagogies. Through ecological metaphors and examples of courageous scholarly collaboration, the article shows how LO can foster interconnectedness, emotional intelligence, and critical consciousness. It proposes a model for recognising LO as a formal interspace in higher education – capable of addressing social fragmentation and supporting global citizenship. By aligning with the values of the Fifth Industrial Revolution and the Sustainable Development Goals, LO is positioned as essential to a more compassionate and just educational future.